Peningkatan Kemanpuan Listening Mahasiswa Sastra Daerah, Indonesia, Ilmu Perpustakaan dan Sastra Inggris Fakultas Ilmu Budaya Melalui Audio Lingual Method - Edward; Hutahaean, Sorta; Fauzi, Mohd (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2024)
This article is entitiled, “The Improvement of Listening Ability of Local, Indonesian, English and Librarianship Study Program Students of Humanities Faculty, Lancang Kuning University. The research was aimed at improving the ability of the students in listening audio discourse. Teaching pronunciation or sound seems to be very fundamental and requires exposure much. Using audio lingual can help improve students’ ability. The result showed that all students succeeded in comprehending the test provided.